Penanaman Karakter Disiplin Pada Anak Usia Dini Melalui Metode Pembiasaan Di Sekolah TK Tri Widodo - Lisa Walgiyati; Syifa Fauziah (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
Instilling the character of discipline in early childhood is an important foundation for shaping orderly behavior, responsibility, and self-control in daily activities. However, in practice, differences in children's levels of discipline are still found, influenced by habits at home, the surrounding environment, and the consistency of rule enforcement at school. This study aims to describe the process of instilling a disciplined character thru habituation methods, as well as to identify the supporting and inhibiting factors in its implementation at TK Tri Widodo Candigaron, Sumowono District, Semarang Regency. The research uses a descriptive qualitative approach. Data were obtained thru participatory observation, in-depth interviews with the school principal (KSGB) and class teachers (GKA), as well as supporting documentation such as daily activity schedules and children's development records. The validity of the data is strengthened thru triangulation of sources and techniques, while the analysis is conducted thru the stages of data reduction, data presentation, and conclusion drawing.The research results show that the instillation of discipline is carried out systematically thru routine habituation integrated into daily activities. The forms of habituation include arriving on time, lining up before entering the classroom, praying before and after activities, adhering to classroom rules, tidying up toys, washing hands before eating, disposing of trash properly, and maintaining time discipline during activity transitions. Supporting factors include teacher role models, clear classroom rules, a conducive school environment, positive reinforcement, and cooperation with parents. The main obstacles include differences in parenting styles, diverse child characteristics, external environmental influences, and limited teaching time.